The Black Sea Region in Modern Russian-Turkish Cooperation: Geo-Strategic Aspect - Alexandr G. Druzhinin (International Journal of Economics and Financial Issues, 2015)
The article builds on analyses of the Post-Soviet trend of Russian-Turkish relations in the Black Sea region while focusing on the features of transnational cooperation in the modern geo-strategic context. The Black Sea region is found to be a priority area of cooperative ties between Russia and Turkey. Revival of Russian presence in this macro-region leads to an increase of the meridional connectivity of this trans-regional space. It is concluded that during the March events of 2014 the deeper mutual unconformity took place between the spheres of Russian geo-strategic interests and the Black Sea segment of the so-called “Turkish World” (i.e., Turk Dunyasi). It is shown that the abandonment of the “South stream” gas project in favor of the “Turkish route” has signifi cantly increased the meridional communication in the Black Sea region. This brings to importance the development of the Russian-Turkish Black Sea coast being as a special geo-economic concept. The gas transportation system is to become its cornerstone with the Istanbul megametropolis being the biggest settlement center of this transnational system.